Porous biological ceramic coating and preparation method thereof
By adding a water-soluble pore-forming agent to the laser cladding powder and removing the pore-forming agent with a water bath to form a uniform pore structure, the problems of laser cladding gun pollution and low repetition rate of porous bioceramic coating in the prior art are solved, and the effect of adjustable pore size and improved bond strength of the ceramic coating is achieved.
Patent Information
- Application Number
- CN202510136600.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, the use of gas escape pore-forming agents can easily cause laser cladding gun contamination during the laser cladding process, resulting in a low repetition rate of porous bioceramic coating.
The water-soluble pore-forming agent is added to the laser cladding powder, and the pore-forming agent is removed through the subsequent water bath heating and dissolution process to form a uniform pore structure. At the same time, by adjusting the dosage of water-soluble pore-forming agent and the temperature and time of water bath heating, the number of pore sizes and distribution in the ceramic coating are controlled.
The problem of laser cladding gun pollution is solved, the pore size adjustability and pore size uniformity of pore bioceramic coatings are improved, and the bonding strength between the coating and the substrate is enhanced.
Smart Images

Figure CN119876940A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of biomaterials, and in particular relates to a porous bioceramic coating and a preparation method thereof. Background Art
[0002] Titanium alloy-based porous bioactive ceramic coatings have attracted the attention of researchers due to their excellent mechanical properties, good bioactivity and pore structure that is conducive to the proliferation and attachment growth of bone tissue cells. They have been reported to have potential applications in the field of bone tissue regeneration and repair.
[0003] Laser cladding technology is an efficient and high-precision surface modification technology. It uses a laser beam to melt powder materials onto the surface of the substrate to form a dense coating. It is widely used in the fields of machinery, aerospace and biomedicine. In recent years, laser cladding technology has also been gradually used to prepare porous ceramic coatings to improve the biocompatibility and functional properties of the coatings.
[0004] The prior art discloses a method for preparing a porous bioceramic coating, which is to add ammonium carbonate, a gas-escape pore-forming agent, to the coating powder, and successfully prepare the porous bioceramic coating by laser cladding technology, which has the characteristics of uniform pore distribution and high pore occupancy of large pores. However, since the added ammonium carbonate is a gas-escape pore-forming agent, when the pore-forming agent is heated, it will escape from the powder. When a laser cladding gun is used to prepare the porous ceramic coating, the laser cladding gun is easily contaminated, resulting in a low reproducibility of the porous bioceramic coating prepared by the laser cladding technology. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a porous bioceramic coating and a preparation method thereof.
[0006] The present invention adds a water-soluble pore-forming agent to the laser cladding powder. Under the high temperature conditions during the laser cladding process, the water-soluble pore-forming agent will not decompose or volatilize; instead, the water-soluble pore-forming agent is removed during the subsequent water bath heating and dissolution process, thereby forming uniform pores in the ceramic coating. This solves the problem of using gas-escape-type pore-forming agents in the prior art, which easily causes the laser cladding gun to be contaminated. The present invention also controls the content and distribution of the pore-forming agent in the ceramic phase generated in situ during the laser cladding process by regulating the amount of the water-soluble pore-forming agent; the ceramic coating is subjected to a water bath heating treatment to form a porous bioceramic coating; and the number and distribution of pores in the porous bioceramic coating are controlled by regulating the hydrothermal temperature and the hydrothermal time, thereby obtaining a porous bioceramic coating with a specific pore size and porosity; and the pore size of the porous bioceramic coating is adjustable and uniform.
[0007] In addition, the present invention selects titanium powder with similar physical properties to the titanium alloy substrate as the main component of the metallurgical transition layer to enhance the metallurgical bonding between the ceramic coating and the metal substrate and play a gradient transition role in the ceramic coating; at the same time, calcium hydrogen phosphate and calcium carbonate composite ceramic powder are selected as the main component of the bioactive ceramic coating to improve the biocompatibility and bioactivity of the ceramic coating; and lanthanum oxide is used as a catalytic component to catalyze the calcium hydrogen phosphate and calcium carbonate composite ceramic powder to generate biologically active components. Titanium powder, calcium hydrogen phosphate and calcium carbonate composite ceramic powder, lanthanum oxide powder and water-soluble pore-forming agent are mixed to obtain multiple precursor powders; each precursor powder is sequentially clad on the surface of the titanium alloy substrate using a laser cladding process to obtain a bioceramic coating with a gradient structure.
[0008] The present invention designs a method of gradually reducing the titanium powder content and gradually increasing the composite ceramic powder content, and adopts a laser cladding process to sequentially clad each precursor powder on the surface of a titanium alloy substrate; so that the titanium powder content decreases layer by layer from the titanium alloy substrate to the bioceramic coating, and the composite ceramic powder increases layer by layer from the titanium alloy substrate to the bioceramic coating, thereby preparing a composite material that gradually transitions from a metal substrate to an inorganic ceramic coating; enhancing the metallurgical bonding between the inorganic ceramic coating and the titanium alloy substrate, and improving the adhesion and overall strength between the coating and the substrate.
[0009] The first object of the present invention is to provide a method for preparing a porous bioceramic coating, comprising the following steps: Step 1: Using titanium powder as the main component for forming a metallurgical transition layer and using composite ceramic powder as the main component for forming a bioactive ceramic layer, the titanium powder and the composite ceramic powder are mixed in a manner such that the titanium powder content decreases gradually and the composite ceramic powder content increases gradually to obtain N mixed powders with different titanium powder and composite ceramic powder contents; and then adding lanthanum oxide powder and a water-soluble pore-forming agent to each mixed powder to obtain N precursor powders with gradient changes.
[0010] It should be noted that the present invention uses titanium powder as the main component of the ceramic coating, and the titanium powder has a wetting effect. At the same time, the titanium powder has good compatibility with the titanium alloy substrate; during the laser cladding process, the titanium powder can enhance the metallurgical bonding between the ceramic coating and the metal substrate, and improve the adhesion and overall strength between the ceramic coating and the substrate. Calcium hydrogen phosphate and calcium carbonate are the main functional components of the ceramic coating. During the laser cladding process, the reaction generates HA and -TCP components with biological activity, which can improve the biocompatibility and biological functionality of the ceramic coating. Preferably, the composite ceramic powder described in the present invention is calcium hydrogen phosphate and calcium carbonate, and the calcium carbonate is 1.4 times the molar amount of calcium hydrogen phosphate. The rare earth oxide lanthanum oxide mainly plays a role in catalyzing the composite ceramic powder of calcium hydrogen phosphate and calcium carbonate to generate HA and -TCP with biological activity during the laser cladding process. At the same time, lanthanum oxide has the effect of refining the grains. Preferably, the mass of the lanthanum oxide powder accounts for 0.5% to 0.7% of the mass of the precursor powder.
[0011] In addition, since the calcium hydrogen phosphate, calcium carbonate, lanthanum oxide and water-soluble pore-forming agent in the precursor powder are all inorganic substances, and the substrate is a titanium alloy, the physical and chemical properties of the inorganic powder in the precursor powder and the substrate are greatly different. Therefore, the present invention designs a plurality of precursor powders; at the same time, according to the content of titanium powder in each precursor powder, the content of composite ceramic powder is gradually reduced; the content of composite ceramic powder is gradually increased in each precursor powder, titanium powder, calcium hydrogen phosphate and calcium carbonate composite ceramic powder, lanthanum oxide powder and water-soluble pore-forming agent are mixed to obtain N precursor powders with gradient changes. Preferably, the value range of N is 2~5, and N is an integer. Preferably, the mass of the titanium powder accounts for 0~70% of the mass of the mixed powder, and the mass of the composite ceramic powder accounts for 30%~100% of the mass of the mixed powder.
[0012] It should also be noted that the present invention adds a water-soluble pore former to the precursor powder. Under the high temperature conditions during the laser cladding process, the water-soluble pore former will not decompose or volatilize; instead, the water-soluble pore former will be removed during the subsequent water bath heating and dissolution process, thereby forming uniform pores in the ceramic coating. Preferably, the water-soluble pore former is sodium chloride. In addition, the present invention also changes the size and distribution of the pores in the ceramic coating by adjusting the amount of the water-soluble pore former added to form a porous structure with a specific pore size and porosity; preferably, the mass of the water-soluble pore former accounts for 10% to 50% of the mass of the precursor powder.
[0013] In order to fully mix the precursor powder, eliminate the agglomeration phenomenon, and ensure the uniform distribution of the precursor powder. The mixing method of the present invention is one of ball milling and mechanical stirring. Since the grinding action of the precursor powder during the ball milling process increases the specific surface area of the precursor powder and improves the reaction activity of the precursor powder, the precursor powder after ball milling is easier to fuse during the laser cladding process to form a uniform and dense ceramic coating structure. In addition, the high-energy impact and grinding action of ball milling can refine large-particle powder into small particles of nanometer or micrometer level, improve the uniformity and dispersibility of the powder; the refined powder is easier to be evenly distributed during the laser cladding process, making the composition and structure of the ceramic coating more uniform and dense. Preferably, the mixing method of the precursor powder is ball milling. Through ball milling, titanium powder, composite ceramic powder, lanthanum oxide powder and water-soluble pore-forming agent can be effectively and evenly dispersed to improve the uniformity and consistency of the precursor powder. Preferably, the mixing time is 8h~10h.
[0014] Step 2: Using a laser cladding process, N precursor powders are sequentially clad on the surface of the titanium alloy substrate in a manner of decreasing the titanium powder content and increasing the composite ceramic powder content, to form a bioceramic coating with a gradient structure.
[0015] The present invention adopts a laser cladding process to sequentially clad each precursor powder on the surface of a titanium alloy substrate to form a multi-layer bioceramic coating that gradually transitions from a metal substrate to an inorganic ceramic coating. The titanium powder content decreases layer by layer from the titanium alloy substrate to each bioceramic coating, and the composite ceramic powder content increases layer by layer from the titanium alloy substrate to each bioceramic coating, forming a bioceramic coating with a gradient structure.
[0016] In the process of preparing bioceramic coating by laser cladding technology of the present invention, laser parameters are one of the key factors affecting the quality and performance of bioceramic coating. Since the laser power determines the temperature and melting depth of the molten pool, it directly affects the melting uniformity and metallurgical bonding effect of the bioceramic coating. Too low power will cause the precursor powder to not be completely melted, forming a non-dense bioceramic coating; too high power may cause the substrate to melt excessively, increase the heat-affected zone and cause deformation of the substrate, affecting the formation of the microporous structure. Preferably, the laser power is 1.5kW~1.8kW. The laser scanning speed affects the heat input and the cooling rate of the molten pool by controlling the moving speed of the laser beam on the surface of the substrate. When the scanning speed is too fast, the bioceramic coating may be discontinuous and the pores may be unevenly formed; when the speed is too slow, the molten pool may be too large, the heat-affected zone of the substrate will increase, and the pore structure of the bioceramic coating will be affected. Preferably, the laser scanning speed is 200mm / min~240mm / min. Because the laser spot diameter affects the laser energy distribution and the size of the molten pool. When the spot is too large, the energy density is insufficient and the powder is difficult to fully melt; when the spot is too small, the energy is concentrated and the molten pool is too deep, which may damage the porous structure of the coating and the integrity of the substrate. Preferably, the diameter of the laser spot is 2 mm to 4 mm.
[0017] Step 3: pretreat the bioceramic coating, and then heat the pretreated bioceramic coating in a water bath to remove the water-soluble pore-forming agent in the bioceramic coating to obtain a porous bioceramic coating.
[0018] It should be noted that the present invention controls the number and distribution of pore sizes in the porous bioceramic coating by regulating the temperature and time of water bath heating, thereby obtaining a porous bioceramic coating with excellent structure and performance. Preferably, the water bath heating temperature is 20°C-100°C. Preferably, the heating time is 2h-12h.
[0019] In addition, the specific operations for pretreatment of the bioceramic coating are as follows: first, the bioceramic coating prepared by laser cladding technology is cut into block shapes, which is conducive to placing the block of bioceramic coating in a beaker for water bath heating; then the coating block is ultrasonically cleaned to remove impurities and residual substances on the cut surface to avoid affecting the dissolution of the water-soluble pore-forming agent during the water bath heating process, thereby affecting the formation of the porous structure; finally, the cleaned coating block is polished with sandpaper with gradually decreasing roughness in turn, cleaned and blown dry to obtain a pretreated bioceramic coating.
[0020] Compared with the prior art, the present invention has the following beneficial effects: The present invention solves the problem of using gas-escape pore-forming agents in the prior art, which causes contamination of the laser cladding gun, by adding a water-soluble pore-forming agent to the precursor powder and utilizing the property that the water-soluble pore-forming agent will not decompose or volatilize under high temperature conditions during the laser cladding process.
[0021] The present invention regulates the amount of water-soluble pore-forming agent, firstly, regulates the number and distribution of pores in the porous bioceramic coating to form a bioceramic coating with adjustable pore size; secondly, improves the bonding strength between the porous bioceramic coating and the substrate. Moreover, the present invention controls the number and distribution of pores in the porous bioceramic coating by regulating the temperature and heating time of the water bath heating, thereby obtaining a porous bioceramic coating with a specific pore size and porosity, and realizing that the pore size of the porous bioceramic coating is adjustable and uniform.
[0022] The present invention mixes titanium powder composite ceramic powder, lanthanum oxide powder and water-soluble pore-forming agent in a manner that the titanium powder content decreases gradually and the composite ceramic powder content increases gradually, so as to obtain a plurality of precursor powders with gradient changes; then, a laser cladding process is adopted, and the plurality of precursor powders are sequentially clad on the surface of the titanium alloy substrate in a manner that the titanium powder content decreases gradually and the composite ceramic powder content increases gradually, so as to form a bioceramic coating with a gradient structure. The present invention uses titanium powder as the main component for forming a metallurgical transition layer to enhance the metallurgical bonding between the ceramic coating and the titanium substrate; and uses calcium hydrogen phosphate and calcium carbonate composite ceramic powder as the main component for forming a bioactive ceramic layer to enhance the biocompatibility and bioactivity of the ceramic coating. At the same time, the titanium powder content decreases layer by layer along the direction from the titanium alloy substrate to each bioceramic coating, and the composite ceramic powder content increases layer by layer along the direction from the titanium alloy substrate to each bioceramic coating, so as to form a bioceramic coating with a gradient structure that gradually transitions from a metal substrate to an inorganic ceramic coating; the metallurgical bonding between the bioceramic coating and the titanium alloy substrate is enhanced, and the adhesion and overall strength between the bioceramic coating and the substrate are improved.
[0023] The porous bioceramic coating prepared by the present invention has a large number of pores, a large pore diameter and a uniform pore distribution; the present invention adopts laser cladding combined with a water bath heating dissolution method to dissolve the pore-forming agent to form pores, and the operation is simple and easy to control. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 XRD patterns of the porous bioceramic coatings prepared in Examples 1 to 5 of the present invention and Comparative Example 1.
[0025] Figure 2 The metallographic microscopic morphology images of the porous bioceramic coatings prepared in Examples 1 to 5 of the present invention and Comparative Example 1; wherein (a) is Comparative Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 1, (e) is Example 4, and (f) is Example 5.
[0026] Figure 3 Surface morphologies of porous bioceramic coatings prepared in Examples 1 to 5 and Comparative Example 1 of the present invention; wherein (a) is Comparative Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 1, (e) is Example 4, and (f) is Example 5.
[0027] Figure 4 Surface morphologies of porous bioceramic coatings prepared in Examples 1 and 6 to 9 of the present invention; wherein (a) is Example 6, (b) is Example 7, (c) is Example 8, (d) is Example 9, and (e) is Example 1.
[0028] Figure 5 Surface morphologies of porous bioceramic coatings prepared in Examples 1 and 10 to 14 of the present invention; wherein (a) is Example 10, (b) is Example 11, (c) is Example 12, (d) is Example 13, (e) is Example 1, and (f) is Example 14. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings.
[0030] In the description of the present invention, unless otherwise specified, all reagents used are commercially available and all methods used are conventional techniques in the art.
[0031] Example 1 This embodiment provides a method for preparing a porous bioceramic coating.
[0032] Step 1: Prepare precursor powder: 1.1) 70 wt.% of titanium powder and 30 wt.% of calcium hydrogen phosphate and calcium carbonate composite ceramic powder are mixed to obtain a mixed powder, wherein the molar amount of calcium carbonate in the composite ceramic powder is 1.4 times that of calcium hydrogen phosphate; with the mixed powder as a matrix, 0.6 wt.% of lanthanum oxide powder and 30 wt.% of sodium chloride are added to the mixed powder, ball milled for 8 h, sieved with a 160 mesh sieve, and dried at 60°C for 12 h to obtain a first precursor powder.
[0033] 1.2) 30 wt.% of titanium powder and 70 wt.% of calcium hydrogen phosphate and calcium carbonate composite ceramic powder are mixed to obtain a mixed powder, wherein the molar amount of calcium carbonate in the composite ceramic powder is 1.4 times that of calcium hydrogen phosphate; with the mixed powder as a matrix, 0.6 wt.% of lanthanum oxide powder and 30 wt.% of sodium chloride are added to the mixed powder, ball milled for 8 hours, sieved with a 160 mesh sieve, and dried at 60°C for 12 hours to obtain a second precursor powder.
[0034] 1.3) Add 0.6 wt. % of lanthanum oxide powder and 30 wt. % of sodium chloride to 100 wt. % of calcium hydrogen phosphate and calcium carbonate composite ceramic powder, wherein the molar amount of calcium carbonate in the composite ceramic powder is 1.4 times that of calcium hydrogen phosphate. After ball milling for 8 h, sieve with a 160-mesh sieve and dry at 60° C. for 12 h to obtain a third precursor powder.
[0035] Step 2: Preparation of bioceramic coating: 2.1) Use a 50 mm × 30 mm × 0.5 mm mold to place the first precursor powder obtained in step 1 on a 50 mm × 30 mm × 10 mm Ti6Al4V substrate.
[0036] 2.2) Using laser cladding equipment, in air atmosphere, the first precursor powder on the surface of the Ti6Al4V substrate was clad at a laser power of 1.8 kW and a scanning speed of 240 mm / s, and the laser beam diameter was controlled to be 4 mm to form a first bioceramic coating.
[0037] 2.3) Use a 50 mm × 30 mm × 0.5 mm mold to place the second precursor powder obtained in step 1 on the first bioceramic coating of 50 mm × 30 mm × 10 mm.
[0038] 2.4) Using laser cladding equipment, in air atmosphere, the second precursor powder on the surface of the first bioceramic coating was clad with a laser power of 1.8 kW and a scanning speed of 240 mm / s, and the laser beam diameter was controlled to 4 mm to form a second bioceramic coating.
[0039] 2.5) Use a 50 mm × 30 mm × 0.5 mm mold to place the third precursor powder obtained in step 1 on the second bioceramic coating of 50 mm × 30 mm × 10 mm.
[0040] 2.6) Using laser cladding equipment, in air atmosphere, the third precursor powder on the surface of the second bioceramic coating was clad with a laser power of 1.8 kW and a scanning speed of 240 mm / s, and the laser beam diameter was controlled to be 4 mm to form a third bioceramic coating to obtain a bioceramic coating.
[0041] Step 3: Preparation of porous bioceramic coating: 3.1) Use a wire cutting machine to cut the bioceramic coating into blocks with a size of 10 mm × 10 mm × 5 mm, which are recorded as coating samples.
[0042] 3.2) The coating samples were ultrasonically cleaned with petroleum ether, acetone, ethanol and distilled water for 20 min respectively.
[0043] 3.3) The cross-section of the cleaned coating sample is polished with metallographic sandpaper with roughness of 120#, 240#, 400#, 800#, 1200#, 1500#, 2000# and 2500# in sequence, and the polished coating sample is cleaned and blown dry to obtain the pretreated coating sample.
[0044] 3.4) The pretreated coating sample was placed in a beaker filled with distilled water and dissolved at 100°C for 10 h to obtain a porous bioceramic coating.
[0045] Example 2 This embodiment provides a method for preparing a porous bioceramic coating.
[0046] The difference between this embodiment and embodiment 1 is: In this embodiment, 10 wt.% of sodium chloride is added to each precursor powder.
[0047] Example 3 This embodiment provides a method for preparing a porous bioceramic coating.
[0048] The difference between this embodiment and embodiment 1 is: In this embodiment, 20 wt.% of sodium chloride is added to each precursor powder.
[0049] Example 4 This embodiment provides a method for preparing a porous bioceramic coating.
[0050] The difference between this embodiment and embodiment 1 is: In this embodiment, 40 wt.% of sodium chloride is added to each precursor powder.
[0051] Example 5 This embodiment provides a method for preparing a porous bioceramic coating.
[0052] The difference between this embodiment and embodiment 1 is: In this embodiment, 50 wt.% of sodium chloride is added to each precursor powder.
[0053] Example 6 This embodiment provides a method for preparing a porous bioceramic coating.
[0054] The difference between this embodiment and embodiment 1 is: The heating temperature in this embodiment is 20°C.
[0055] Example 7 This embodiment provides a method for preparing a porous bioceramic coating.
[0056] The difference between this embodiment and embodiment 1 is: The heating temperature in this embodiment is 40°C.
[0057] Example 8 This embodiment provides a method for preparing a porous bioceramic coating.
[0058] The difference between this embodiment and embodiment 1 is: The heating temperature in this embodiment is 60°C.
[0059] Example 9 This embodiment provides a method for preparing a porous bioceramic coating.
[0060] The difference between this embodiment and embodiment 1 is: The heating temperature in this embodiment is 80°C.
[0061] Example 10 This embodiment provides a method for preparing a porous bioceramic coating.
[0062] The difference between this embodiment and embodiment 1 is: The heating time in this embodiment is 2h.
[0063] Embodiment 11 This embodiment provides a method for preparing a porous bioceramic coating.
[0064] The difference between this embodiment and embodiment 1 is: The heating time in this embodiment is 4 hours.
[0065] Example 12 This embodiment provides a method for preparing a porous bioceramic coating.
[0066] The difference between this embodiment and embodiment 1 is: The heating time in this embodiment is 6 hours.
[0067] Embodiment 13 This embodiment provides a method for preparing a porous bioceramic coating.
[0068] The difference between this embodiment and embodiment 1 is: The heating time in this embodiment is 8 hours.
[0069] Embodiment 14 This embodiment provides a method for preparing a porous bioceramic coating.
[0070] The difference between this embodiment and embodiment 1 is: The heating time in this embodiment is 12 hours.
[0071] Comparative Example 1 This comparative example provides a method for preparing a bioceramic coating.
[0072] The difference between this comparative example and Example 1 is: No sodium chloride was added in this comparative example.
[0073] Comparative Example 2 This comparative example provides a method for preparing a porous bioceramic coating.
[0074] Step 1: Prepare precursor powder: 70wt.% of titanium powder and 30wt.% of calcium hydrogen phosphate are mixed with calcium carbonate composite ceramic powder to obtain a mixed powder, wherein the molar amount of calcium carbonate in the composite ceramic powder is 1.4 times that of calcium hydrogen phosphate; with the mixed powder as a matrix, 0.6wt.% of lanthanum oxide powder and 30wt.% of sodium chloride are added to the mixed powder, ball milled for 8h, sieved with a 160-mesh sieve, and dried at 60°C for 12h to obtain a precursor powder.
[0075] Step 2: Preparation of bioceramic coating: 2.1) Use a 50 mm × 30 mm × 0.5 mm mold to place the first unit precursor powder obtained in step 1 on a 50 mm × 30 mm × 10 mm Ti6Al4V substrate.
[0076] 2.2) Using laser cladding equipment, in air atmosphere, the first unit precursor powder on the surface of the Ti6Al4V substrate was clad with a laser power of 1.8 kW and a scanning speed of 240 mm / s, and the laser beam diameter was controlled to 4 mm to form a bioceramic coating.
[0077] Step 3: Preparation of porous bioceramic coating: 3.1) Use a wire cutting machine to cut the bioceramic coating into blocks with a size of 10 mm × 10 mm × 5 mm, which are recorded as coating samples.
[0078] 3.2) The coating samples were ultrasonically cleaned with petroleum ether, acetone, ethanol and distilled water for 20 min respectively.
[0079] 3.3) The cross-section of the cleaned coating sample is polished with metallographic sandpaper with roughness of 120#, 240#, 400#, 800#, 1200#, 1500#, 2000# and 2500# in sequence, and the polished coating sample is cleaned and blown dry to obtain the pretreated coating sample.
[0080] 3.4) The pretreated coating sample was placed in a beaker containing distilled water and dissolved at 100°C for 10 h to obtain a porous bioceramic coating.
[0081] Experimental test: 1. XRD characterization The present invention performs XRD phase structure analysis on the porous bioceramic coatings prepared in Examples 1 to 5 and Comparative Example 1.
[0082] Figure 1 The XRD patterns of the porous bioceramic coatings prepared in Examples 1 to 5 and Comparative Example 1 are shown in FIG. Figure 1 It can be seen that in Examples 1 to 5 and Comparative Example 1, sharp diffraction peaks appear in the XRD patterns at 2θ=27.5°, 33°, 47°, 59°, and 69.5°. 2 )、01-1055(CaTiO 3 )、72-1243(Ca 10 (PO 4 ) 6 (OH) 2 、89-1949(CaTiO 3 ) search and analysis, the main phases of the porous bioceramic coatings prepared in Examples 1 to 5 and the bioceramic coating prepared in Comparative Example 1 are TiO 2 and CaTiO 3 The calcium phosphate bioceramic phase and Ca 5 (PO 4 ) 3 The non-calcium phosphate bioceramic phases of Cl and β-TCP indicate that the addition of pore-forming agents does not significantly affect the phase structure of the bioceramic coating.
[0083] 2. Metallographic analysis The present invention uses an IX41M metallographic microscope to perform metallographic testing on the porous bioceramic coatings prepared in Examples 1 to 5 and Comparative Example 1, with a magnification of 10X to 400X, a lighting system of 12V / 50W xenon lamp, an output voltage of 15V / 13.4A, and a stage movement range of 50mm×50mm. The results are as follows Figure 2 shown.
[0084] Figure 2 The metallographic microscopic morphology of the porous bioceramic coating prepared in Examples 1 to 5 and Comparative Example 1; wherein (a) is Comparative Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 1, (e) is Example 4, and (f) is Example 5. Figure 2 As shown in (a), there are a large number of transverse and longitudinal cracks on the porous bioceramic coating, and there are obvious holes in the metallurgical bonding area of the cross section, indicating that the bonding degree of the bioceramic coating of Comparative Example 1 is low; Figure 2(b) also has many longitudinal cracks, transverse cracks and obvious holes, indicating that when 10wt.% sodium chloride pore-forming agent is added, the bonding degree between the porous ceramic coating and the substrate is low; Figure 2 In (c), there are fewer cracks on the porous bioceramic coating, and the ceramic layer and the alloy layer are dense, indicating that the ceramic layer is well bonded to the substrate. Figure 2 There are almost no obvious cracks in the porous bioceramic coating in (d), and the ceramic layer and the alloy layer are dense, indicating that when 10wt.% sodium chloride pore-forming agent is added, the porous bioceramic coating has a good bonding degree with the substrate. Figure 2 In (e), there are many holes, transverse cracks and longitudinal cracks on the porous bioceramic coating and alloying layer, and the structure is very loose, with poor bonding; Figure 2 In (f), there are many holes and cracks in the porous bioceramic coating and the alloying layer, indicating that the bonding degree between the coating and the substrate is poor. This shows that when a certain amount of pore-forming agent sodium chloride is added, the bonding strength between the porous bioceramic coating and the substrate and the size of the coating tissue can be improved, while excessive pore-forming agent will destroy the bonding strength between the coating and the substrate. The present invention forms a bioceramic coating with a certain pore structure by adding 10wt.% to 30wt.% of sodium chloride pore-forming agent, and can enhance the bonding strength between the bioceramic coating and the substrate.
[0085] 3. Surface morphology analysis The present invention uses a Japanese Hitachi S-3400N SEM to characterize the morphology of the porous bioceramic coatings prepared in Examples 1 to 15, with an operating voltage of 15 kV. The results are as follows: Figure 3~Figure 5 shown.
[0086] Figure 3 The surface morphology of the porous bioceramic coating prepared in Examples 1 to 5 and Comparative Example 1; (a) is Comparative Example 1, (b) is Example 2, (c) is Example 3, (d) is Example 1, (e) is Example 4, and (f) is Example 5. It can be seen from the figure that when no pore-forming agent is added, the number of pores formed in the porous bioceramic coating is small and the pore size is small. As the amount of pore-forming agent added gradually increases, such as Figure 3 As shown in (b), the pore size of the porous bioceramic coating gradually increases, but the number of pores is still small, and only a small number of pores with increased pore size are found in some areas; Figure 3 As shown in (c), the pore distribution area of the porous bioceramic coating is significantly increased, but the pore size distribution is uneven; Figure 3As shown in (d), the pores of the porous bioceramic coating are evenly distributed in each area, with a large number of pores and a large pore depth. When the amount of pore former reaches 40%, the pores of the porous bioceramic coating are more distributed, but most of the pores are loosely organized stacked pores with small pore diameters and low pore depths; when the amount of pore former continues to increase, when the amount of pore former reaches 50%, the pores in the porous bioceramic coating do not change much, and most of the pores are loosely organized stacked pores. This shows that when the amount of pore former is 30%, and the pore former is removed by heating and dissolving in a water bath for 10 hours, the number of pores is large, the pore diameter is large, and the pore distribution is uniform.
[0087] Figure 4 The surface morphology of the porous bioceramic coating prepared in Example 1 and Example 6 to Example 9; wherein (a) is Example 6, (b) is Example 7, (c) is Example 8, (d) is Example 9, and (e) is Example 1. Figure 4 As can be seen from (a) in the figure, when the heating temperature is 20°C, the number of pores dissolved from the porous bioceramic coating is small and the pore size is small; as the temperature increases, Figure 4 As shown in (c) and (d), the number of pores dissolved from the porous bioceramic coating gradually increases, and the pore size gradually increases; when the hydrothermal temperature is 100°C, the number of pores in the porous bioceramic coating is large, the pore size is large, and the pore distribution is uniform. This shows that when the heating temperature is 20°C to 100°C, the present invention can prepare a porous bioceramic coating with a certain number of pores, and the preferred heating temperature of the present invention is 20°C to 100°C; when the hydrothermal temperature is 100°C, the number of pores in the porous bioceramic coating is large, the pore size is large, and the pore distribution is uniform, and the more preferred heating temperature of the present invention is 100°C.
[0088] Figure 5 The surface morphology of the porous bioceramic coating prepared in Example 1 and Example 10 to Example 14; wherein (a) is Example 10, (b) is Example 11, (c) is Example 12, (d) is Example 13, (e) is Example 1, and (f) is Example 14. Figure 5 As can be seen from (a) in the figure, when the heating time is 2 h, the number of pores dissolved from the porous bioceramic coating is small and the pore size is small; as the heating time increases, Figure 5 As shown in (c) and (d) in the figure, the number of pores dissolved from the porous bioceramic coating gradually increases, and the pore size gradually increases; when the heating time is 6h and 8h, as shown in Figure 5 As shown in (c) and (d), the number of pores in the porous bioceramic coating continues to increase, but most of them are loosely packed pores; when the heating time is increased to 10h, the number of pores in the porous bioceramic coating increases significantly and the pore size is large; continue to extend the heating time, such as Figure 5As shown in (f), the number and pore size of the porous bioceramic coating do not change much. This shows that the present invention can prepare a porous bioceramic coating with a certain number of pores when the heating time is 2h~12h, so the preferred heating time of the present invention is 2h~12h; when the heating time is increased to 10h, the number of pores in the porous bioceramic coating increases significantly and the pore size is large; the more preferred heating time of the present invention is 10h.
[0089] The mechanical property test shows that compared with the single-layer porous bioceramic coating prepared in Comparative Example 2, the porous bioceramic coating with a gradient structure prepared in Example 1 has a higher bonding force, indicating that the present invention forms a bioceramic coating with a gradient structure on the surface of the titanium alloy substrate, gradually transitioning from the metal substrate to the inorganic ceramic coating, thereby enhancing the metallurgical bonding between the bioceramic coating and the titanium alloy substrate, thereby improving the adhesion and overall strength between the bioceramic coating and the substrate.
[0090] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, once those skilled in the art know the basic creative concept, they can make other changes and modifications to these embodiments, and these changes and modifications all fall within the scope of the present invention.
[0091] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. If these modifications and variations of the present invention fall within the scope of the equivalent technology of the present invention, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a porous bioceramic coating, characterized in that: The following steps are involved: Using titanium powder as the main component for forming a metallurgical transition layer and using composite ceramic powder as the main component for forming a bioactive ceramic layer, the titanium powder and the composite ceramic powder are mixed in a manner that the titanium powder content decreases gradually and the composite ceramic powder content increases gradually to obtain N mixed powders with different titanium powder and composite ceramic powder contents, and then adding lanthanum oxide powder and a water-soluble pore-forming agent to each mixed powder to obtain N precursor powders with gradient changes; Using a laser cladding process, N precursor powders are sequentially clad on the surface of the titanium alloy substrate in a manner in which the titanium powder content decreases gradually and the composite ceramic powder content increases gradually, so as to form a bioceramic coating with a gradient structure; The bioceramic coating is pretreated, and then the pretreated bioceramic coating is heated in a water bath to remove the water-soluble pore-forming agent in the bioceramic coating to obtain a porous bioceramic coating.
2. The method for preparing the porous bioceramic coating according to claim 1, characterized in that: The water-soluble pore-forming agent is sodium chloride.
3. The method for preparing the porous bioceramic coating according to claim 1, characterized in that: The value range of N is 2 to 5, and N is an integer.
4. The method for preparing the porous bioceramic coating according to claim 1, characterized in that: The mass of the water-soluble pore-forming agent accounts for 10% to 50% of the total mass of the precursor powder; the mass of the lanthanum oxide powder accounts for 0.5% to 0.7% of the total mass of the precursor powder.
5. The method for preparing the porous bioceramic coating according to claim 1, characterized in that: The heating temperature is 20° C. to 100° C., and the heating time is 2 h to 12 h.
6. The method for preparing the porous bioceramic coating according to claim 1, characterized in that: The mass of the titanium powder accounts for 0-70% of the mass of the mixed powder; the content of the titanium powder decreases layer by layer from the titanium alloy substrate to the bioceramic coating.
7. The method for preparing the porous bioceramic coating according to claim 1, characterized in that: The composite ceramic powder is calcium hydrogen phosphate and calcium carbonate; the mass of the composite ceramic powder accounts for 30% to 100% of the mass of the mixed powder; and the content of the composite ceramic powder increases layer by layer from the titanium alloy substrate to the bioceramic coating.
8. The method for preparing the porous bioceramic coating according to claim 1, characterized in that: The laser power of the laser cladding process is 1.5 kW to 1.8 kW, the laser scanning speed is 200 mm / min to 240 mm / min, and the laser spot diameter is 2 mm to 4 mm.
9. The method for preparing a porous bioceramic coating according to claim 1, characterized in that: The pretreatment process is to cut, clean and grind the bioceramic coating.
10. A porous bioceramic coating prepared by the method for preparing a porous bioceramic coating according to any one of claims 1 to 9.